(untitled) (Bangladesh Journal of Medical Science, 2025)
When it comes to cancers of the head and neck, oral squamous cell carcinoma (OSCC) ranks high. Its complicated and poorly known molecular pathways underlie its genesis and progression. An essential role in cancer aetiology is played by long non-coding RNAs (lncRNAs), which have recently come to light as key regulators of gene expression. The purpose of this article is to offer a thorough analysis of the functions of three long non-coding RNAs (lncRNAs) in relation to oral squamous cell carcinoma: HOTTIP, HOTAIR, and MALAT1. BJMS, Volume: 24. Supplementary Issue 2025, Page : 34-38